UV photoprotection of Osthol. Issue 11 (1st December 2016) - Mir, Feroz A.; Khan, Shoukat H.
ABSTRACT: In the present paper, Osthol (molecular formula: C15 H16 O3 ; molecular mass: 244) was obtained from the plant Prangos pabularia by column chromatography technique. This compound was simultaneously exposed to short- (254 nm) and long-wavelength (365 nm) ultraviolet (UV) radiations for different time periods. These irradiated samples were characterized by UV–Visible spectroscopy. No significant variation in optical absorbance/transmittance in broad (200–365 nm) spectrum is observed with increasing dose. The effect of temperature on optical absorption is also insignificant. Effect of UV radiation and temperature on optical band gap ( Eg ), Urbac energy, or disorder energy ( Eu ) was also analyzed. A small impact on these optical parameters ( Eg and Eu ) was observed. This molecule seems very stable (at molecular level) under the influence of UV radiations and temperature. These observed properties shown by this compound projects it as a potential UV protection material.